Hydro-mechanical coupled modeling of hydraulic fracturing using the mesh fragmentation technique - Cleto, Pedro R. [UNESP]; Manzoli, Osvaldo L. [UNESP]; Sánchez, Marcelo; Maedo, Michael A.; Beserra, Leila B.S.; Guimarães, Leonardo J.N. (Elsevier, 2020)
The inclusion of special interface elements between standard finite elements is becoming a common technique to model discontinuities in porous media using the finite element method (FEM). Recently, it was proved that high aspect ratio (HAR) elements can reproduce very satisfactorily the main features of behavior observed in a single hydraulically-induced fracture. In this paper, the mesh fragmentation technique (MFT) is proposed to extend the application of HAR elements to simulate more general problems involving the formation of hydraulic fractures in rocks by introducing this type of element in-between the standard FE of a typical mesh. The proposed framework makes use of standard FE techniques. Therefore, it is relatively easy to upgrade an existing FE program for continuous porous media to deal with evolving discontinuities. The proposed approach is verified and validated against available analytical and numerical solutions. The crack patterns predicted by the MFT are also compared with the ones observed in the laboratory. The formation of multiple fractures is also analyzed. In all cases, the proposed technique was able to properly capture the main features of rock behavior subjected to hydraulic fracturing.
Keywords: Finite elements with high aspect ratio; Hydraulic fracturing; Hydro-mechanical coupling; Mesh fragmentation technique